Hubungan Tingkat Pengetahuan Tentang Dismenore Terhadap Sikap Remaja Putri Dalam Penanganan Dismenore di SMA Muhammadiyah Tanah Grogot - Wahyuni, Desti Tri; Rahman, Gajali; Lushinta, Lidia (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2024)
Knowledge of young women about dysmenorrhoea in Indonesia is still quite low, so many young women do not know how to treat dysmenorrhoea properly and correctly. The purpose of this study was to determine the relationship between the level of knowledge about dysmenorrhea and the attitude of adolescent girls in dealing with dysmenorrhea. This research method is cross sectional, the population was all teenage girls in class X and XI at SMA Muhammadiyah Tanah Grogot Paser Regency. The sampling technique with a total sampling of 55 people. The results of this study showed a significant relationship between the level of knowledge of dysmenorrhea and the attitude of young women in dealing with dysmenorrhea by obtaining (p-value = 0.000). which means a relationship between the level of knowledge on the attitude of adolescent girls in the treatment of dysmenorrhea.